Implementation and Evaluation of User Experience on Mobile Augmented Reality Technology-Based Brochure Applications - Aulia Akhrian Syahidi; Arifin Noor Asyikin; Rahimatus Sania; Subandi Subandi (Universitas Hamzanwadi, 2021)
Along with the spread of the COVID-19 virus which has an impact on new student admissions at various universities in Indonesia. This impact was also felt at the Politeknik Negeri Banjarmasin (POLIBAN) with the decline in the number of registrants and the public's interest in continuing higher education. So we need a promotion that is not monotonous and must be innovative. Various kinds of technology have been created to support and facilitate all activities in various fields, one of which is in the field of promotional media. Promotion is very important for a university to offer or show the facilities and infrastructure contained in the university and show its quality. The purpose of this study is to implement mobile augmented reality technology as a POLIBAN promotional media solution and evaluate the user experience of the application. The research method used is the Extreme Programming (XP) development method and a technique for evaluating user experience using the User Experience Questionnaire (UEQ). The results of the research conducted based on the results of the implementation stated that functionally all the features offered by the application can function properly and the results of the evaluation of user experience as a non-functional assessment of 50 respondents with an average value of 2.87 with an excellent predicate.